The use of eplerenone in therapy‐resistant chronic central serous chorioretinopathy - Myrte B. Breukink; Anneke I. den Hollander; Jan E.E. Keunen; Camiel J.F. Boon; Carel B. Hoyng (2014)
With interest we read the article by Tsai and colleagues (Tsai et al. 2013) describing an increased risk of being diagnosed with erectile dysfunction in males with central serous chorioretinopathy (CSC). In this article, it is hypothesized that vascular obstruction due to endothelial dysfunction may be an underlying mechanism in CSC. Strikingly, an inappropriate activation of the mineralocorticoid receptor, found in the choroidal vasculature (endothelial and smooth muscle cells), has also been recently suggested to underlie the pathogenesis of CSC (Zhao et al. 2012). This study also suggested a reduction in subretinal fluid (SRF) level in two patients by systemic use of eplerenone, a selective mineralocorticoid receptor antagonist, implying that eplerenone could be a promising treatment. Here we report the treatment outcome with oral eplerenone in five patients suffering from chronic CSC, who experienced persistent SRF on spectral-domain optical coherence tomography (OCT) for at least 9 months and responded insufficiently to previous treatments. Oral administration of eplerenone 25 mg/day was started at baseline. At the start of week 2, eplerenone was increased to 50 mg/day and completely stopped at the end of week 5, according to the previously described protocol (Zhao et al. 2012). A fixed follow-up protocol was used with visits scheduled at baseline, 1, 3, 5 weeks and a final examination after 10 weeks. The five patients (three males) had a mean age of 55 years (range 41–64 years), and two patients had bilateral active chronic CSC. None of the patients had a history of steroid use. A full reduction of SRF on OCT was seen in patient 1 (Fig. 1A). In this patient, there was only a minor increase in visual acuity (VA), which is most likely the result of the prolonged detachment of the neurosensory retina, causing irreversible damage to the photoreceptors (Wang et al. 2002). Patient 2 initially had a decrease in SRF but then relapsed after cessation of the eplerenone treatment (Fig. 1B). Patient 3 showed a decrease in subfoveal SRF, but showed an increase in SRF inferior of the fovea (Fig. 1C). Patient 4 had no change in SRF, nor a clear effect on VA (Fig. 1D). Patient 5 had bilateral active disease, in which one eye first had a decrease in SRF which then returned to baseline-level, whereas an increase in SRF occurred in the other eye (Fig. 1E). The use of eplerenone did not influence the hyperfluorescent pattern, typical for chronic CSC, that was seen in all patients on fluorescein angiography and indocyanine green angiography. None of the patients showed a change in subfoveal choroidal thickness on enhanced-depth-imaging-OCT during the course of the study, and systemic parameters remained within normal range in all patients. Curative therapeutic options for chronic CSC are scarce and the current leading options consist of photodynamic therapy treatment, conventional laser treatment, or micropulse laser treatment, with anatomical success rates in photodynamic therapy treatment ranging from 60 up to 100% (Quin et al. 2013). A lack of response to these treatment modalities is not uncommon. Zhao and colleagues (Zhao et al. 2012) described that an overstimulation of the mineralocorticoid receptor in a rat model caused dilation of the choroidal vasculature and choroidal thickening, similar to clinical observations in chronic CSC. The same group recently presented promising results in 13 patients with CSC, showing a full reduction of SRF in 25% of the patients at 1 month and 67% at 3 months after use of eplerenone (Bousquet et al. 2013). However, the current pilot study indicates that eplerenone has a beneficial effect only in a minority of patients with long-standing treatment-resistant chronic CSC. The precise role of an inappropriate activation of the mineralocorticoid receptor in chronic CSC therefore remains controversial. This study was supported by the following foundations: 'Stichting MD Fonds', 'Gelderse Blindenstichting', 'Landelijke Stichting voor Blinden en Slechtzienden' and 'Oogfonds' that contributed through 'UitZicht' and the 'JANIVO Stichting'. The funding organizations had no role in the design or conduct of this research. No author has any financial/conflicting interests in the products mentioned in the article.